2021
DOI: 10.3389/fbioe.2020.611684
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Zirconia Surfaces Regulate Human Gingival Fibroblasts Behavior Through Differential Modulation of Macrophage Polarization

Abstract: Zirconia exhibits excellent biocompatibility and is widely used as dental implant materials in prosthodontics. Over the past years, research and development of dental implant biomaterials has focused on osseointegration, but few reports exist regarding the role of the immune environment on cellular responses to these materials. The present study investigates the effect of different nanostructured zirconia surface topographies on macrophage phenotypes and their influence on gingival fibroblast behavior. Three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Wang et al (172) used the antioxidant drug quercetin onto nano-octahedral ceria to inhibit M1 polarization, promote M2 polarization, and the nanocomposites exhibit scavenging of ROS in an animal model of periodontitis. Wu et al (173) were able to modify the behavior of macrophages against gingival fibroblasts by modifying the zirconia surface, providing a new method for restoring periodontal soft tissue attachment after repair therapy. In implant-related studies, Yang et al (174) guided macrophage adhesion by constructing a micro/nanomesh and found that M2 polarization and angiogenesis was promoted.…”
Section: Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (172) used the antioxidant drug quercetin onto nano-octahedral ceria to inhibit M1 polarization, promote M2 polarization, and the nanocomposites exhibit scavenging of ROS in an animal model of periodontitis. Wu et al (173) were able to modify the behavior of macrophages against gingival fibroblasts by modifying the zirconia surface, providing a new method for restoring periodontal soft tissue attachment after repair therapy. In implant-related studies, Yang et al (174) guided macrophage adhesion by constructing a micro/nanomesh and found that M2 polarization and angiogenesis was promoted.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Wu et al. ( 173 ) were able to modify the behavior of macrophages against gingival fibroblasts by modifying the zirconia surface, providing a new method for restoring periodontal soft tissue attachment after repair therapy. In implant-related studies, Yang et al.…”
Section: Immunoregulatory Treatment Of Periodontitis Associated With Macrophage Polarizationmentioning
confidence: 99%
“…In practical applications, the implantation of biomaterials inevitably triggers some immune cell-mediated immune responses, and the immune responses play an important role in releasing pro- or anti-inflammatory factors to regulate angiogenesis and bone formation. − As an immune cell, the phenotype and function of macrophages are capable of polarizing responses to changes in the local physiological microenvironment, thereby maintaining local tissue homeostasis . Macrophages can polarize into pro-inflammatory (M1) and anti-inflammatory (M2) macrophage phenotypes, starting with M1 macrophages by releasing pro-inflammatory factors such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) that trigger initial defensive inflammation, followed by M2 macrophages through the release of anti-inflammatory factors such as the transforming growth factor-β (TGF-β), interleukin-4 (IL-4), and interleukin-10 (IL-10) that induce favorable physiological microenvironments for osteogenesis, improve inflammatory response and secrete factors to promote angiogenesis and bone tissue regeneration, and accelerate the bone regeneration process .…”
Section: Introductionmentioning
confidence: 99%
“…In that, macrophages are recognized as forerunners to discern and respond to foreign biomaterials (Miron and Bosshardt, 2016;Ogle et al, 2016). During the early stages after implantation of biomaterials, the macrophages migrate to the implant area and differentiate into the pro-inflammatory M1 phenotype (classical type), triggering the defensive inflammation by the release of pro-inflammatory molecules, such as interleukin (IL)-1, tumor necrosis factor (TNF)-α and inducible nitric oxide synthase (iNOS) (Wu et al, 2020). The phenotype plasticity allows macrophages to switch into different phenotypes in response to distinct material signals (Miron and Bosshardt, 2016;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%